Management of oligometastatic ovarian cancer recurrence during PARP inhibitor maintenance. Issue 9 (22nd July 2022) - Palluzzi, Eleonora; Marchetti, Claudia; Cappuccio, Serena; Avesani, Giacomo; Macchia, Gabriella; Gambacorta, Maria Antonietta; Cocciolillo, Fabrizio; Scambia, Giovanni; Fagotti, Anna
Abstract : Objective: The benefit of surgery and maintenance treatment with PARP inhibitors (PARPi) has been clearly demonstrated in ovarian cancer. Also, the efficacy and safety of stereotactic body radiotherapy has been shown in patients with metastatic, persistent, and recurrent disease. The aim of this study is to evaluate the management of oligometastatic progression during PARPi maintenance treatment. Methods: This is an observational, retrospective, single-arm study conducted from June 2017 to December 2020 in patients with recurrent ovarian cancer with oligometastatic progression under PARPi maintenance treatment and receiving surgery or stereotactic body radiotherapy for such recurrence. PARPi treatment was continued until further progression of the disease. The primary objective of the study was the median prolongation of the treatment-free interval-p (without platinum) after local treatment. Results: A total of 186 patients with ovarian cancer were treated with PARPi at recurrence. Of these, 30 (16%) developed oligometastatic progression. The median age was 49.5 years (range 35–73). Olaparib, niraparib and rucaparib were administered to 33%, 60%, and 7% of patients, respectively. The median prolongation of the treatment-free interval-p of patients treated with surgery or stereotactic body radiotherapy was 6 and 10 months, respectively (p=0.53). The median treatment-free interval-p of patients treated with surgery or stereotactic body radiotherapy at the time of oligometastatic progression was 32 and 29 months, respectively (p=0.44). At the time of this publication, 50% of patients are still on treatment with PARPi following progression. Conclusions: Patients with recurrent ovarian cancer who have oligometastic progression during PARPi maintenance may continue to benefit from PARPi if combined with local treatment.